FULFILLMENT OF POLITICAL RIGHTS OF VULNERABLE GROUPS WITH DISABILITIES AND INCLUSIVE ELECTION STEPS IN 2024 IN LEIHITU DISTRICT, CENTRAL MALUKU REGENCY - Jeane Talakua (Media Inovasi Pendidikan dan Publikasi, 2023)
The right steps that must be taken by election organizers for people with disabilities in the political system as a 'disability perspective' will teach this nation the importance of the human side. Because balanced policies for every citizen who has diverse backgrounds and conditions will also be needed. Inclusive steps that must be taken by the government of election organizers in Central Maluku Regency, especially Leihitu District towards the disabled voter group, which according to data is 140 people with special needs for each person in order to participate in the election process in 2024. The first step is to define the type of disability in order to make it easier to fulfill the rights of each vulnerable group of voters with disabilities. The second step is for people with disabilities to receive a polling station that suits their individual needs in Leihitu Sub-district. The third step is to create social sensitivity in all circles of society. The fourth step needs to be considered is Supervision as one of the election organizing institutions that have supervisory duties must have a tiered strategy. The fifth step is socialization and advertising that can be accessed by people with disabilities in every village in Leihitu District. There needs to be improvements at the level of implementers in the field that must be adapted to the needs of each vulnerable group of voters with disabilities.